A study on nucleation, crystallization kinetics, microstructure and mechanical properties of Ru–Bi partial substituted BSCCO glass ceramics - Gokcen, T.; Ozturk, O.; Cavdar, Şükrü; Koralay, Haluk; Tasci, A. T. (Springer Science and Business Media LLC, 2015)
This study deals with the effects of Ru–Bi partial substitutions on the thermal, structural and mechanical properties of Bi1.8−x Ru x Pb0.2Sr2CaCu2O10+δ (x = 0.0, 0.025, 0.050, 0.075) system, produced by using glass ceramics method. The effects of Ru–Bi partial substitutions on glass transition, nucleation and crystallization temperature were analyzed via differential thermal analyzer (DTA). Besides, microstructure and micromechanical properties of Ru–Bi partially substituted BSCCO glass ceramics were also investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and Vickers microhardness measurements. From the DTA results, nucleation kinetics were studied by using Ozawa, Augis–Bennett, Takhor and Kissinger equations. In addition to this, activation energies and Avrami parameters were also calculated. According to the results of the thermogravimetric analyses, the amount of oxidation was seen to be increased with increasing Ru concentration. Moreover, the lattice parameters, volume fractions and surface morphologies of our newly produced glass ceramics were investigated by XRD and SEM measurements, respectively. RISE behavior obtained from the microhardness measurements for all samples. Microhardness, elastic modulus, yield strength and fracture toughness values decreased with increasing Ru doping.